Stabil: An educational Matlab toolbox for static and dynamic structural analysis. Issue 5 (16th February 2021) - François, Stijn; Schevenels, Mattias; Dooms, David; Jansen, Miche; Wambacq, Jef; Lombaert, Geert; Degrande, Geert; De Roeck, Guido
Abstract: The capability to analyze structures under static and dynamic loads is an essential skill for structural engineers. Structural analysis therefore is a key component in civil and architectural engineering education, where analytical methods are traditionally complemented by the use of (commercial) software packages. The latter are often closed source, which may obscure the links to the underlying matrix structural analysis or finite element formulation. To stimulate active, cooperative, and solution‐oriented learning, we developed Stabil, an electronic learning environment implemented as a Matlab toolbox. Stabil has an open structure to elucidate the links between theory and implementation and is presently used throughout the curricula of Civil and Architectural Engineering at KU Leuven. This paper explains the main principles of Stabil and discusses teaching experiences over the past 15 years. Stabil can be downloaded from http://bwk.kuleuven.be/bwm/stabil .